MICROFLUIDIC CELL FOR OPTICAL RESONATOR ARRAY SENSOR - A. V. Saetchnikov; E. A. Tcherniavskaia; V. A. Saetchnikov; A. .. Ostendorf (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
Microfluidic cell containing spherical optical sensor array has been developed. Fluid dynamics simulation has shown that the cell provides a high degree of homogeneity of the analyte flow. Test experiments for biological environmental changes detection inside the cell has been performed.